PHYSICOCHEMICAL CONDITIONS OF CRYSTALLIZATION OF LATE CENOZOIC VOLCANIC ASSOCIATIONS IN THE LESSER CAUCASUS - Imamverdiev N.A. (My University, 2003)
Various geothermometers were used to determine the physicochemical conditions (temperature, pressure, and oxygen fugacity) of crystallization of Late Cenozoic volcanic rocks in the Lesser Caucasus. The first data are obtained on the composition of the parental magmas of each association, the melting degree of the mantle source is assayed, along with the role of mantle metasomatism in the genesis of the magmas. The evolutionary trajectories of the melts of each volcanic association are determined, and the conclusion is made that the evolutions of the andesite-dacite-rhyolite and trachybasalt-trachyandesite associations were controlled by crystallization differentiation, while the rocks of the trachyrhyolite association were derived from the granite-metamorphic crustal layer.
Keywords: Cenozoic; Cenozoic; Кайнозой